Vaporization characteristics of 1-propanol droplets at high temperatures - Saharin, Sanisah; Lefort, Benoite; Morin, Celine; Chauveau, Christian; Le Moyne, Luis; Kafafy, Raed (2011)

(untitled)
The gasification of a droplet via vaporization is one of the main processes in combustion systems, namely diesel and propulsion engines. In these combustion systems, always the liquid fuel is atomized as a cloud of droplets in the chamber, which then vaporizes, and mixes with the oxidant and burns to release heat. Therefore, to afford a better knowledge especially in modelling complex spray flows and mixture formation issues, the study of the droplet vaporization which involves mass, heat and momentum transfer processes is really vital. Alcohol has been chosen for this particular study due to its potential as an alternative fuel to the current conventional hydrocarbon fuel. However, viability of alcohols as alternate fuels has been limited by their high latent heat of vaporization and low heating value which can deliver difficulty in providing rapid gasification, mixing and ignition. Consequently, the objective of this study is to provide more data and understanding in alcohols vaporization behaviour. Methanol and ethanol have been studied extensively in terms of fundamental issues such as vaporization, in engine performances and pollutants formation. However, the potential is now extended and shifted on propanol, which has a better energy density and lower affinity with water than methanol and ethanol. A detailed description of the vaporization of an isolated droplet has been realized in this experimental study aimed at investigating another aliphatic alcohol, 1-propanol. This investigation extended our previous study on ethanol droplet vaporization to 1-propanol that is known as always less volatile, but holds higher boiling point than ethanol. The characterization of the vaporization phenomenon is necessary for this liquid fuel to develop efficient design of injection systems for propulsion and power generation. Particularly, the vaporization rates and their dependency on temperature, important features for modeling and design, are explored for 1-propanol for the first time at high temperatures. The experimental set-up consists of a pressure chamber in which the furnace, the droplet formation, the droplet support and motion devices are located. To minimize the influence of the droplet supporting system, a cross quartz fibers (14 μm) configuration has been used. A 1-propanol droplet is located at the intersection of the cross with a controlled initial diameter (400 – 600 μm). Ambient temperature is varied from 298 to 973 K, whereas the ambient pressure is maintained at atmospheric pressure. The temporal evolution of the droplet squared diameter of 1-propanol exhibits a quasi-steady behaviour. The result shows that the d2-law is apparently obeyed and a constant vaporization rate is achieved. The histories of the instantaneous vaporisation rates calculated from the d² (t) curves which are almost always a constant confirm this quasi stationary aspect of the phenomenon. However, as the ambient temperature increased beyond 673 K, the instantaneous vaporization rate decreases slightly during the droplet lifetime. It could be said that at higher temperatures, the vaporization of 1- propanol droplet show a slightly different behaviour.